From Cocoa to Chocolate: The Impact of Processing on In Vitro Antioxidant Activity and the Effects of Chocolate on Antioxidant Markers In Vivo - Di Mattia, Carla D.; Sacchetti, Giampiero; Mastrocola, Dino; Serafini, Mauro (Frontiers in Immunology, 2017)
Chocolate is a product processed from cocoa rich in flavonoids, antioxidant compounds and bioactive ingredients that have been associated to both its healthy and sensory properties. Chocolate production consists of a multi-step process which, starting from cocoa beans, involves fermentation, drying, roasting, nib-grinding and refining, conching and tempering. During cocoa processing, the naturally occurring antioxidants (flavonoids) are lost, whilst others, such as Maillard reaction products, are formed. The final content of antioxidant compounds and the antioxidant activity of chocolate is a function of several variables, some related to the raw material and others related to processing and formulation. The aim of this mini review is to revise the literature on the impact of full processing on the in vitro antioxidant activity of chocolate, providing a critical analysis of the implications of processing on the evaluation of the antioxidant effect of chocolate in in vivo studies in humans.